Perancangan Ulang Tata Letak Fasilitas Pabrik di Pabrik Roti Bobo Bakery - misra hartati (JTI: Jurnal Teknik Industri, 2015)
Problems found in Bobo Bakery Bread Factory is the placement and arrangement of the room were irregular and not in accordance with the process flow, resulting in the production process flow perpotongnya barriers. Distance much room for further activities are also deemed less effective and efficient. Planning the layout of the proposed improvement Bobo Bakery Bread Factory uses the type of facility layout is based on production flow. The flow pattern of material or material that should be applied is the flow pattern u. In designing the layout of the proposal, there is a change in dosing stations as well as increasing the number of machines in the mixing station, cooling, and packaging as much as each of the three machines mixer, 7 and 2 engine cooling fan packaging. Increasing the number of these machines is based on the calculation of the engine needs. Distance total displacement of the material before improvement of 21.5 meters, while the total distance of the proposed improvements obtained material displacement by 19 meters.Perancangan Ulang Tata Letak Fasilitas Pabrik  Di Pabrik Roti Bobo Bakery